A synthesis of Mexican mammalogy in Therya: the first 10 years! - Reyes Díaz, Jorge Luis; López González, Carlos A.; Kelt, Douglas A.; Vargas Cuenca, Julieta; Lara Díaz, Nalleli E. (THERYA, 2021)
Mammalogy as a discipline was pursued in Mexico since the mid-17th century. However, Mexican researchers were involved primarily in the mid-20th century, when national scientific journals were established to emphasize research on mammals. In 2010, the Asociación Mexicana de Mastozoología, A. C., initiated the journal Therya. Therya has now completed its first decade of publication, and in this work, we analyze the articles and scientific notes published in Therya, focused on the studies of mammals in Mexican territory, including researchers and institutions, to describe the path that mammalogy has taken in recent years in Mexico. This synthesis therefore serves as a frame of reference for future mammalogy studies. We compiled all papers published in Therya during the period 2010-2019. We built a database gathering information from these publications such as authors, institutions and states of origin, study areas, capture methods, topics and taxa studied. We excluded from the analyses research outside of Mexico. We did a descriptive statistics analysis including mean, proportions, percentage and trends for each and all the sections. Therya has published 181 articles and 52 scientific notes on mammals distributed in Mexico. The majority of authors and institutions were from Mexico City. The states of southeastern Mexico were the most used as a study area, particularly Oaxaca and Chiapas. The orders Carnivora and Cetartiodactyla were the most studied, mainly using indirect methods. Trapping methods were most commonly used for small mammals. The least studied orders were Eulipotyphla, Cingulata, and Pilosa. The most studied topics are ecology, diversity, conservation and distribution. Therya has become one of the most important journals about mammal research in Mexico. Research in mammalogy, as reflected in the pages of Therya, is based in academic institutions with the metropolitan area of Mexico City, reflecting the institutional infrastructure and age, and possibly institutional budgetary factors. The southeast portion of the country is well studied due to the existence of regional institutions, as well as to the concentration of high biodiversity. The least studied regions of Mexico may be the result of a reduced number of research groups and social insecurity. Much research is focused on small mammals, making Sherman traps and mist nets the most used trapping methods; carnivores and cetartiodactyls are the most studied groups, using indirect study methods reducing study costs and effort. Ecology, diversity and distribution are the most studied topics, these studies allow the development of management plans.